Defamiliarizing the Familiar: Avant-Garde and Archivism in the Songs of the Residents. Issue 2 (4th May 2021) - Butler, Martin
ABSTRACT: This article argues that the Residents' songs are defined by both an avant-gardist and an archival momentum. While their music goes beyond established patterns of pop, iit also "stores" musical forms and themes by mashing up references from commercial(ized) popular music, distorted to different degrees of (un)recognizability. Thus defamiliarizing the familiar, the Residents articulate a particular metareferential stance on popular musical production and reception, irritating generic conventions and audience expectations. In so doing, the band indeed takes an avant-gardist position characterized by transgression and innovation, but also entailing a conservative momentum that contributes to stabilizing (pop-) cultural memory and tradition.